133k views
2 votes
How would you do this problem?

How would you do this problem?-example-1
User Lospejos
by
6.0k points

1 Answer

5 votes

Answer:

Explanation:

Recall that the equation of the most basic parabola is y = x^2.

The first illustration shows a parabola that has been translated two units to the right. Modify the basic equation as follows:

y = x^2 => y = (x - 2)^2.

The second illustration is similar, except that the graph of y = x^2 has been translated 2 units to the left:

y = x^2 => y = (x + 2)^2

User Gs Hurley
by
5.0k points